A New Species of Mites of the Genus Geckobia (Prostigmata, Pterygosomatidae), Parasitic on Mediodactylus kotschyi (Reptilia, Gekkota) from Crimea - Bertrand, M.; Kukushkin, O.; Pogrebnyak, S. (Вестник зоологии, 2013)
Geckobia sharygini Bertrand, Kukushkin et Pogrebnyak, sp. n., a parasite of gecko Mediodactylus kotschyi danilewskii (Strauch, 1887) collected from Crimea (Ukraine) is described. The new species differs from other species of the genus by the scutum with convex posterior edge and seven pairs of dorsal stout setae on scutum. Almost 89?% of mites were found on the ventral surface of lizard’s body. Maximum observed parasite charge is 60 specimens for a synanthropic locality and 17 mites for a natural locations. With exception of the newborn lizards, the infestation slightly increased from spring to autumn. The improved key to Pterygosomatidae and some Geckobia is provided. Position of G. sharygini sp. n. and some related species in the genus Geckobia is discussed in connection with phylogeny, distribution and ecological peculiarities of the hosts.